The Business Judgment Rule in State-Owned Enterprise: Legal Pluralism of Islamic, State and Customary Law - Meli Pransiska Simanjuntak; Muhammad Arifin; Zainuddin Zainuddin (Hukum Keluarga Islam IAIN LANGSA, 2025)
The strengthening of the Business Judgment Rule through Law Number 16 of 2025 concerning the Fourth Amendment to Law Number 19 of 2003 concerning State-Owned Enterprises (SOEs) has not fully eliminated the tension between the corporate law regime and the state finance regime in determining the limits of liability for the board of directors of SOEs. This research aims to analyze the post-reform regulatory construction of the Business Judgment Rule and to reconstruct the directors' liability standards through a legal pluralism approach. This study employs a normative legal research method with statutory and conceptual approaches, utilizing descriptive-analytical and prescriptive techniques to qualitatively analyze primary and secondary legal materials. The findings indicate that formal-positivistic legislative amendments alone are insufficient to resolve this paradigm conflict. Consequently, this research develops the